ANALISIS UPAYA HAMBATAN DAN SOLUSI GURU DALAM MENUMBUHKAN 8 DIMENSI PROFIL LULUSAN DI SD INPRES SIKUMANA 3 - Filipus Rasul Rosari Nasir; Firda Ariyani Amir; Sindi Rotlis Magdalena Beba; Chantika Seventin Desemberina Doke; Nana Naysila Cynthia Nahak; Rony Arianto Tanesab; Vera Rosalina Bulu; Marfelano Bessie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine teachers’ efforts, challenges, and solutions in fostering the eight dimensions of the Graduate Profile, as well as the impact of its implementation on students at UPTD SD Inpres Sikumana 3. The study employed a quantitative approach using a survey method, with data collected through Likert-scale questionnaires administered to teachers and fifth-grade students. The data were analyzed using descriptive statistics, including the number of respondents (N), minimum score, maximum score, mean, and standard deviation. The findings indicate that teachers’ efforts in fostering the eight dimensions of the Graduate Profile are categorized as high, while the challenges faced by teachers are at a moderate level. Meanwhile, the solutions implemented by teachers are categorized as very high, reflecting strong professional commitment in overcoming existing challenges. In addition, the implementation of the Graduate Profile shows a positive impact on students, which is categorized as high, particularly in terms of character development, learning attitudes, and basic competencies. Overall, this study demonstrates that consistent teachers’ efforts supported by effective solutions play a crucial role in optimizing the implementation of the Graduate Profile in elementary schools.